The Effectiveness Of Interactive Learning Powerpoint Media To Increase Knowledge Of Dental Health In B Group Of TKIT Permata Hati Ngaliyan Semarang - Harditya, Denty; Mukminin, Amirul (BELIA: Early Childhood Education Papers, 2018)
Dental health is an important part of overall health. In children, the disease and tooth decay can lead to adverse consequences for growth, for it takes considerable knowledge so that children can take care of their teeth. One great way to increase the knowledge of the child's teeth in the current era is to provide play activities and learning with technology is through interactive media powerpoint.The problem in this research is whether interactive learning media powerpoint effective in increasing knowledge of dental health of children at the age of 5-6 years. This study aims to determine the effectiveness of interactive learning powerpoint media increase knowledge of dental health in children at age 5-6 years.             The research was conducted in TKIT Ngaliyan Semarang Permata Hati using the form Pre-experimental design to approach one group pretest-posttest design. The samples used were children aged 5-6 years as many as 32 children. The technique of taking samples in this research is technique. purposive sample Analysis of the data used is the method Until Independent t-Test.             The calculation result data showed an increase in values  mean originally became 126.3 88.13. The amount of the increase that occurred at 38.25. Based on calculations using paired t-Test Sample obtained values - ttable> t> ttable,namely (- 2,039> - 21 534 or 21 534> 2,039), with sig = 0.000. A significant difference can be seen from two tailed sig <0.05 is 0.000 or Sig. (2-tailed) <0,05 so Ha received and H0 is rejected.             It can be concluded that by using interactive powerpoint media could increase knowledge of dental health in children at age 5-6 years